Control of murine brown adipocyte development by GATA6 - Jun, Seoyoung; Angueira, Anthony R; Fein, Ethan C; Tan, Josephine M E; Weller, Angela H; Cheng, Lan; Batmanov, Kirill; Ishibashi, Jeff; Sakers, Alexander P; Stine, Rachel R; Seale, Patrick (Developmental cell, 2023)
Brown adipose tissue (BAT) is a thermogenic organ that protects animals against hypothermia and obesity. BAT derives from the multipotent paraxial mesoderm; however, the identity of embryonic brown fat progenitor cells and regulators of adipogenic commitment are unclear. Here, we performed single-cell gene expression analyses of mesenchymal cells during mouse embryogenesis with a focus on BAT development. We identified cell populations associated with the development of BAT, including Dpp4+ cells that emerge at the onset of adipogenic commitment. Immunostaining and lineage-tracing studies show that Dpp4+ cells constitute the BAT fascia and contribute minorly as adipocyte progenitors. Additionally, we identified the transcription factor GATA6 as a marker of brown adipogenic progenitor cells. Deletion of Gata6 in the brown fat lineage resulted in a striking loss of BAT. Together, these results identify progenitor and transitional cells in the brown adipose lineage and define a crucial role for GATA6 in BAT development.